Tipifications of 22 names of Apiaceae subfamily Saniculoideae from southern South America - Calviño, Carolina Isabel; Martínez, Susana Graciela (Phytotaxa, 2019)
Typification (the selection of a permanent reference specimen to a name) is necessary for the correct identification of plant species, and requires an expert knowledge of the taxonomic group under study and of the nomenclatural rules. While preparing the treatment for Flora of Argentina, names of Apiaceae subfamily Saniculoideae were found to need typification. These names include species of Eryngium and Sanicula. To resolve these typifications, protologues and the original material of all names were studied, and decisions were made following the International Code of Nomenclature for Algae, Fungi, and Plants (Shenzhen Code). As a result, 20 lectotypifications and three neotypifications are designated here, giving justifications for each selection.